2007
DOI: 10.3748/wjg.v13.i4.564
|View full text |Cite
|
Sign up to set email alerts
|

Protection ofVeratrum nigrum L. var. ussuriense Nakai alkaloidsagainst ischemia-reperfusion injury of the rat liver

Abstract: AIM:To investigate the protective effects and possible mechanisms of Veratrum nigrum L.var. ussuriense Nakai alkaloids (VnA) on hepatic ischemia/reperfusion (I/R) injury in rats. METHODS:Forty male Wistar rats were randomly divided into four experimental groups (n = 10 in each): (A) Control group (the sham operation group); (B) I/R group (pretreated with normal saline); (C) Small-dose (10 mg/kg) VnA pretreatment group; (D) Large-dose (20 mg/kg) VnA pretreatment group. Hepatic ischemia/ reperfusion (Hepatic I/R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The induction and maintenance of inflammation requires the adhesion of lymphocytes to target cells. Con A induces direct biological change in hepatocytes, resulting in hepatic injury by activated lymphocytes 18 . The pro‐inflammatory state is an early step in the inflammatory cascade that promotes the attraction, adherence and subendothelial migration of mononuclear cells to the liver 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The induction and maintenance of inflammation requires the adhesion of lymphocytes to target cells. Con A induces direct biological change in hepatocytes, resulting in hepatic injury by activated lymphocytes 18 . The pro‐inflammatory state is an early step in the inflammatory cascade that promotes the attraction, adherence and subendothelial migration of mononuclear cells to the liver 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Con A induces direct biological change in hepatocytes, resulting in hepatic injury by activated lymphocytes. [18] The pro-inflammatory state is an early step in the inflammatory cascade that promotes the attraction, adherence and subendothelial migration of mononuclear cells to the liver. [16] The expression of the adhesion molecules is a hallmark event in the development of the pro-inflammatory state in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…VN has ability to cause nausea and vomiting, it is applied to dyspnea in epilepsy or stroke patients8. Studies have revealed that VN can decrease blood pressure and heart rate in hypertensive rats9, and it affords significant protection against hepatic ischemia/reperfusion injury in rats10.…”
mentioning
confidence: 99%